“Influencia de cepas de trichoderma sp endofito en el crecimiento, nutrición y resistencia foliar a phytophthora palmivora en plantones de cacao (theobroma cacao L.) en San Martín)” - Pichis García, Roger Aban Hader (2013)
This research has developed in the field of plant pathology at the lnstitute of Tropical Crops - Tarapoto (ICT - T) located in Shilcayo district, province and region of San Martin - Peru. This study aimed to determine the influence of strains of Trichoderma sp endophyte on growth, foliar nutrition and resistance to Phytophthora palmivora in cocoa seedlings (Theobroma cacao L.) in the greenhouse, using cocoa IMC- 67 clone. 14 treatments were considerad, of which four of them used individual strains of Trichoderma Nº. 17, 22, 91 and 126, is also conducted strain combinations in dual form in six treatments was conducted also a combination of all strains (Treatment 11) and used three controls (Treatments 12, 13 and 14). In this research, we conducted three inoculations with strains of Trichoderma sp via drench, the first day of planting, the second at 45 days after sowing (dds), and the third was at 90 dds, using a suspension of 1x106 cfu/g soil. To obtain the results were evaluated, plant height, stem diameter, number of leaves, leaf area, root length, total biomass, nutrient content and leaf resistance to Phytophthora palmivora, which was used discs leaves inoculated with drops containing zoosporas density 2x105 mr1 . The results of this study show that Treatment 4 (TE -126), obtained better results, being a biological alternativa for the control of Phytophthora palmivora, making this study, a large contribution to organic agricultura. Keywords: Trichoderma, inoculation, strains, Phytophthora, leaf resistance.